Low-temperature directed crystallization as a realization of Green Chemistry principles. - Eksperiandova, L.P. (Functional Materials, 2016)
It is proposed a hybrid method for determination of water using low temperature directed crystallization. The length of the opaque upper part of obtained ice ingot depends on total salinity of water and serves as an analytical signal. Simultaneously the presence of dominant anions can be visually determined by configuration of the opaque part. The concentrate of micro-impurities localized after the crystallization in the upper part can be separated from the ice ingot and left to the following analysis. The method is compared favorably with such standard methods as gravimetry and conductometry used for water salinity determination. The reagentless method complies with the principles of Green Chemistry, since its application does not lead to pollution of the environment.